Metodologia para monitoramento da mortalidade empresarial, e sua aplicação nas empresas de base tecnológica de São Carlos - Oliveira, Meire Ramalho de (Universidade Federal de São Carlos, 2012)
This dissertation presents a proposed methodology for monitoring corporate mortality, and some results of its use to evaluate the mortality of technology-based companies in São Carlos, SP. The proposed methodology comprises 12 steps, and provides guidelines for defining the criteria for characterization of mortality (Stage I), selection of sources of information (Stages II and III), choice of the period of observation (Stage V), construction of the universe of research (Stages VII and VIII), determining rates of mortality (Stage XI), and identification of causes of death (Stage XII). The methodology also guides actions for routine monitoring of corporate mortality, and to compare results. The methodology was applied to evaluate the mortality of technology-based companies in São Carlos. The universe of the research was formed by the companies created by the year 2005, organized in four entries, namely ParqTec, GETEC, PIPE, and São Carlos. The criterion used for mortality was the formal closure, as detected in the JUCESP (Board of Trade of São Paulo State), and Internal Revenue Service taxpayer number (CNPJ). The period of observation of mortality ranged between 2006 and 2010. The following mortality rates were obtained: 5.2% of the companies from ParqTec established by 2005 formally ended their activities from 2006 to 2010. Similarly, the mortality was 6.8% of GETEC register, PIPE 0% and the rate of São Carlos register was 5.6%. The causes of death were explored by consulting the leaders of the companies closed. Due to the small number of responses, 8 questionnaires, the results regarding causes of death should not be regarded as conclusive. The methodology contributes primarily to guide the process of designing and implementing research to evaluate business mortality, to guide the choice of methodological alternatives, and comparing results.
Keywords: Empreendedorismo; Empresas - mortalidade; Empresas de base tecnológica; Empresas - taxas de mortalidade; Empresas - causas de mortalidade; São Carlos (SP); Metodologia; ParqTec; GETEC; PIPE; Business Mortality; Technology-based Enterprises; Methodology; São Carlos; ParqTec; GETEC; PIPE; Mortality rate; Causes of mortality; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO